EFFECT OF DIETANOLAMIDE (DEA) SURFACTANT ADDITION AND DEEP-SEA BACTERIA ACTIVITIES ON THE BIODEGRADABILITY OF ARTIFICIAL OILY WASTEWATER IN SEAWATER MEDIA - Syafrizal Syafrizal; Rendy Budi Prastiko; Tri Partono; Yanni Kussuryani (Scientific Contributions Oil and Gas, 2018)
Marine oil spills have bad impacts on the marine biota. Oil spill mitigation that is currently safe, effi cient, relatively cheap and easy to implement is bioremediation, that is degradation of oil spills biologically using microorganisms. Petroleum will be more easily dispersed in water when surfactants are added. The surfactants have the ability to increase the bioavailability of petroleum to facilitate bacteria contact with carbon sources as their feed. This study was intended to test the effect of addition of diethanolamide (DEA) surfactants to improve the ability of bacteria to degrade hydrocarbon compound in the seawater media. The biodegradation experiment was conducted in 8-liter seawater media and the ability of DEA surfactants to reduce surface tension, oil content, pH and nutrients on days 0, 1, 3, 6 and 10 were observed. GC-MS analysis was conducted to detect chemical component changes in petroleum. A bacterial consortium of Enterobacter sp., Pseudomonas sp., and Raoultella sp. was utilized. The oil was degraded up to 65.52% with biodegradation rate k = -0.1054 t in the media added with DEA surfactants. The aliphatic fraction detected was C17-C31 n-alkane compound and after biodegradation it became C20- C31. The results showed that DEA surfactants were able to improve the ability of bacterial consortium to degrade petroleum.